A inclusão de alunos surdos em escolas regulares: Desafios para o ensino de Biologia - Pimenta, Francis Laine Felisbino (Universidade Federal de São Carlos, 2023)
Inclusive education aimed at deaf students has undergone many changes in recent years, especially in relation to legislation that guarantees access and permanence of deaf students in Brazilian schools, but there are still some barriers to be overcome. The objectives of this research consist of describing and analyzing the possible challenges encountered both by teachers in the area of Biological Sciences and by deaf students, describing which strategies and didactic resources were used and applied in the classroom, knowing the legislation regarding the theme , to analyze the role of the Libras interpreter and its possibilities in helping deaf students and, finally, to present perspectives and possibilities for the teaching-learning of this discipline. The methodology developed in this work was a qualitative bibliographical research, based on scientific publications in the period of 2011 and 2020, regarding the challenges faced by professionals who work in teaching Biology to deaf students. As a result, it was found that despite the legal guarantees that determine the inclusion of deaf students in Brazilian schools, conditions are still lacking for inclusive education to become Biology truly inclusive a reality in our country.
The inclusion of deaf students in regular schools: Challenges for Biology teaching
Keywords: Surdos; Inclusão; Ensino de Biologia; Legislação; Deaf; Inclusion; Biology Teaching; Legislation; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO